Genomic characterisation of putative growth hormone releasing hormone (GHRH) receptor genes in the teleost fish Fugu rubripes - Cardoso, João CR (2014)
The genomic organisation of a putative GHRH receptor gene has been characterised in the teleost fish, Fugu rubripes. It comprises 13 exons and is at least 1.2 3 larger than previously described vertebrate GHRH receptors. Sequence conservation with other vertebrate GHRH receptors is highest over the seven transmembrane domains with preservation of 8 conserved cysteines and an N-glycosylation site in the N-terminal region, which are important for receptor activation. Database mining revealed a further putative GHRH receptor in Fugu, with phylogenetic tree topology indicating that this was potentially a teleost-specific duplication event. This is the first time that the genomic organisation of a GHRH receptor gene has been characterised from a nonmammalian vertebrate.